Nodular lymphocyte predominant Hodgkin's lymphoma in daily practice: A multicenter experience. Issue 1 (14th July 2017) - Gemici, Aliihsan; Aydogdu, Ismet; Terzi, Hatice; Sencan, Mehmet; Aslan, Alma; Kaya, Ali Hakan; Dal, Mehmet Sinan; Akay, Meltem Olga; Dogu, Mehmet Hilmi; Ayyildiz, Orhan; Sahin, Fahri; Cagliyan, Gulsum Akgun; et al.
Abstract: Nodular lymphocyte predominant Hodgkin's lymphoma (NLPHL) is a rare subtype of Hodgkin's lymphoma. In this study, we aimed to investigate the clinical features and therapeutic outcomes of patients with NLPHL who were diagnosed at different institutes in Turkey. We retrospectively reviewed the records of the patients diagnosed with NLPHL. Adult patients who were diagnosed after 2005 with histological confirmation were selected for the study. Forty‐three patients were included in the study. Median age of patients was 37.5 years (18‐70) at the time of diagnosis. About 60.5% patients were diagnosed as stage I and II NLPHL, and remaining 39.5% had stage III and IV disease. Median follow‐up was 46 months. During follow‐up, none of the patients died. Seven patients relapsed or progressed after initial therapy at a median of 12 months. Five of 7 relapsed/refractory patients (71.4%) were salvaged with chemotherapy only (DHAP, ICE), and the remaining 2 (28.6%) were salvaged with chemoimmunotherapy. All of relapsed/refractory patients were able to achieve complete remission after salvage therapy. Lactate dehydrogenase levels were significantly higher in patients with progressive disease compared with nonprogressive disease. Our study showed an excellent outcome with all patients alive at last contact with a median follow up of 46 months despite a wide range of different therapeutic approaches. All relapsed and refractory patients were successfully salvaged despite a low frequency of patients received immunotherapy in conjunction with chemotherapy. Our results suggest that immunotherapy may be reserved for further relapses.